2005
DOI: 10.1093/jn/135.10.2329
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-8 Is Involved in Water Transport in Isolated Superficial Colonocytes from Rat Proximal Colon

Abstract: Water is an essential nutrient because it must be introduced from exogenous sources to satisfy metabolic demand. Under physiologic conditions, the colon can absorb and secrete considerable amounts of water even against osmotic gradients, thus helping to maintain the body fluid balance. Here we describe studies on both aquaporin (AQP) expression and function using cells isolated from the superficial and lower crypt regions of the rat proximal colon. The expression of AQP-3, -4, and -8 in isolated colonocytes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 40 publications
3
51
0
1
Order By: Relevance
“…In mammals, AQP7 has a relatively narrow tissue distribution, and focus has been on the role as a glycerol channel in association with adipose and liver tissue (Rodríguez et al, 2011). AQP7 is also expressed in the apical brushborder of the rat small intestine, where it may play a role in water movement in the apical domain of enterocytes (Laforenza et al, 2005); in the apical membrane of rat proximal straight tubules, where its role may be in water absorption or urea secretion, thus participating in the concentrating mechanism of the mammalian kidney (Ishibashi et al, 2000a); and finally, AQP7 was localized in the plasma membrane of skeletal muscle fibers (Wakayama et al, 2004), where its function is as yet unknown.…”
Section: Research Articlementioning
confidence: 99%
“…In mammals, AQP7 has a relatively narrow tissue distribution, and focus has been on the role as a glycerol channel in association with adipose and liver tissue (Rodríguez et al, 2011). AQP7 is also expressed in the apical brushborder of the rat small intestine, where it may play a role in water movement in the apical domain of enterocytes (Laforenza et al, 2005); in the apical membrane of rat proximal straight tubules, where its role may be in water absorption or urea secretion, thus participating in the concentrating mechanism of the mammalian kidney (Ishibashi et al, 2000a); and finally, AQP7 was localized in the plasma membrane of skeletal muscle fibers (Wakayama et al, 2004), where its function is as yet unknown.…”
Section: Research Articlementioning
confidence: 99%
“…The intracellular immunolocalization of Aqp8aa(1+2) in both the liver and intestine of Atlantic salmon resonates well with earlier findings of AQP8 in mammals. For example, vesicular localization of AQP8 has been reported in rat kidney tubules (Elkjaer et al 2001) and subapical localization in the jejunum and duodenum (Elkjaer et al, 2001;Laforenza et al, 2005;Tritto et al, 2007), with intracellular localization noted in colonic enterocytes and hepatocytes (Elkjaer et al, 2001). The hepatic vesicular localization in rat was confirmed in a study by García et al (García et al, 2001), who further demonstrated that cAMP was a strong stimulus for redistribution of the protein to the plasma membrane.…”
Section: Cellular and Subcellular Localization Of Salmon Aquaporin 8 mentioning
confidence: 81%
“…It was reported that Aqp8 was essential component of cell membrane and was involved in water transport (Ma et al, 1997), and inhibition of Aqp8 expression by siRNA significantly decreased osmotic water permeability in isolated colonocytes (Laforenza et al, 2005). So, it seems siRNA transfection for Aqp8 may induce alterations of water transport and cellular osmolarity in hepatic cells.…”
Section: Discussionmentioning
confidence: 96%